Lecture Notes in Computer Science
DOI: 10.1007/978-3-540-76725-1_32
|View full text |Cite
|
Sign up to set email alerts
|

Robust Color Contour Object Detection Invariant to Shadows

Abstract: Abstract. In this work a new robust color and contour based object detection method in images with varying shadows is presented. The method relies on a physics-based contour detector that emphasizes material changes and a contourbased boosted classifier. The method has been tested in a sequence of outdoor color images presenting varying shadows using two classifiers, one that learnt contour object features from a simple gradient detector, and another that learnt from the photometric invariant contour detector.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The authors concluded that for detecting and discriminating all color groups, there is no single optimal color space. Scandaliaris et al (2007) reported the color and contour-based object detection. They used RGB, C1C2C3, and o1o2 color space images to show the robustness of their models in changing the illumination and varying shadows.…”
Section: Related Workmentioning
confidence: 99%
“…The authors concluded that for detecting and discriminating all color groups, there is no single optimal color space. Scandaliaris et al (2007) reported the color and contour-based object detection. They used RGB, C1C2C3, and o1o2 color space images to show the robustness of their models in changing the illumination and varying shadows.…”
Section: Related Workmentioning
confidence: 99%
“…The invariant gradient detector that we propose is based on the work of Gevers [8] and the modifications proposed in [7]. This detector uses three color models that have different and complementary properties regarding their response: RGB, c1c2c3 and o1o2.…”
Section: A Color Modelsmentioning
confidence: 99%
“…One way to eliminate these maxima is propagating the uncertainties associated to the color models as well as the different gradient moduli. In order to do this, we calculate the gradient magnitude of the RGB, c1c2c3 and o1o2 color models, and then, we propagate (see [7] for details) the RGB uncertainties, assumed to be known, through the various color models up to the gradient magnitudes, using the uncertainties associated with the gradient magnitude of each color space, σ ∇ C . Finally we define the gradient product…”
Section: B Color Invariant Gradientmentioning
confidence: 99%
See 2 more Smart Citations